2017
DOI: 10.3138/cart.52.1.3636
|View full text |Cite
|
Sign up to set email alerts
|

Where Is It (in the Map)? Recall and Recognition of Spatial Information

Abstract: Findings of empirical studies of spatial memory using maps are direct responses to the successful transfer and processing of map information. The memory performance of map users is an important indication of the quality of a map design. Studies of spatial memory have mainly relied on recall performances, but maps can be used in various ways depending on the map user's task and applied strategy. Therefore, one memory paradigm does not cover the entire spectrum of options for examining the retrieval of map infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 44 publications
1
15
0
1
Order By: Relevance
“…Thus, we assume that the relation between location memory performance and map complexity has an inverse u-shape (cf. [19]). Future experiments could investigate this assumption by investigating location memory performance in maps with extensively high visual complexity.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, we assume that the relation between location memory performance and map complexity has an inverse u-shape (cf. [19]). Future experiments could investigate this assumption by investigating location memory performance in maps with extensively high visual complexity.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…In case of topographical maps empirical evidence exists showing that object location memory performance improves with increasing map complexity [17][18][19]. These authors also found that artificial map elements (grids) added to a map improve object location memory performance, especially in maps with low complexities.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Empirical research of cartography, spatial cognition and experimental psychology has recently led to some recommendations for the construction of user cognition-oriented cartographic media. For example, it was reported in user experiments that an additional layer of square grids increases the performances in memory of object locations (Bestgen et al 2017;Kuchinke et al 2016;Edler et al 2014) and in estimating longer linear distances in maps (Dickmann et al 2019). The grid-based memory effect also occurs if the grid structure is physically reduced to indicated ("illusory") lines (Dickmann et al 2017), gets a depth offset or is changed to a hexagonal pattern (Edler et al 2018c).…”
Section: The Potential Of Ar Techniques For Experiencing Spacementioning
confidence: 99%